Income and disbursement of Urban Local Bodies: A Study of Kurnool Municipal Corporation - Muniswami, Samadri (International Journal of Scientific Research and Management (IJSRM), 2018)
The ancient India which was famous for its ‘village republics’, was also a land of big and well administered cities and towns. The excavations of Harappa and Mohenjodaro have brought out the remains of well-run cities. Kautilya, in His renowned treatise on ‘Arthshastra’, has given a graphic description of the city of Patliputra, the capital of the great Mauryas, and its administration. Megasthenese, the Greek ambassador to the court of Chandra Gupta Maurya, has also left a description of the city of Patliputra. The cities continued to flourish under the Muslim rule and reached the peak of their glory under the Mughals. The Britishers also developed cities like Bombay, Calcutta and Madras. This trend towards growing urbanization has continued unabated since 1947. The later half of the twentieth century has witnessed a marked shift of population from rural to urban areas. The accelerated growth of rate in urban population is the natural consequence of modernization and industrialization to which we are committed. “Search for security of life and property, greater employment opportunities, better amenities of life and just glamour are the main factors responsible for this exodus from rural to urban areas.” This growing urbanization has affected not only economic structure of the country but also its ‘social and cultural profiles’